INFORMATION SYSTEM DESIGN IN THE SUPPLY OF GOODS CV. CITRA ARTHA BUANA - Ricky Yun Efren Nelson Vinansius S.L.T; Eko Hadiyanto. SSi. MM (Jurnal Sistem Informasi, 1999)
A system can be said to be good, if the system can provide the required informationquickly and accurately. From the analysis that the author did in the inventory systemused by CV. Citra Artha Buana, there are several obstacles, among others, on thecontrol system is out of goods and goods in, handling returns of goods, inventory anddifficulties in collecting data from the relevant sections. Therefore, for the smoothprogress of work and the company needs to make a better sys tem.